Growth of pigmented rice (Oryza sativa L. Cv. Riceberry) exposed to ZnO nanoparticles - Samart, Sutichai; Chutipaijit, Sutee (My University, 2019)
Exposure of plants to nanomaterials has been evaluated to the positive and negative effects on crop growth, metabolism, and productivity. In this research, application of zinc oxide (ZnO) nanoparticles was studied in pigmented rice (Oryza sativa L. cv. Riceberry). Riceberry plants were grown and irrigated for 60 days. After that, Riceberry plants were exposed to ZnO nanoparticles by treating them with 0, 200, 400 or 800 mg L-1 of ZnO nanoparticles. The plant heights, plant weights, numbers of panicles/clump, photosynthetic pigment contents, and antioxidant enzyme activities were determined. Results showed that 200 mg L-1 of ZnO nanoparticles induced the high enhancement of plant heights, plant weights, numbers of panicles/clump, total photosynthetic pigment contents, and antioxidant enzyme activities as compared to 400 mg L-1, 800 mg L-1 of ZnO nanoparticles and the control (0 mg L-1 of ZnO nanoparticles) treatments. Moreover, the contents of anthocyanin accumulation in the rice seeds exposed to ZnO nanoparticles were measured. The seeds of Riceberry plants exposed to 200 mg L-1 of ZnO nanoparticles exhibited higher the accumulation of anthocyanin contents than other treatments (0, 400 and 800 mg L-1 of ZnO nanoparticles). It was observed that the appropriation of ZnO nanoparticle concentrations may play a role in enhanced the plant growth, productivity and metabolite of Riceberry plants.
Keywords: Anthocyanin; Metabolite; Plant growth; Riceberry; ZnO nanoparticles